Different activities of Schinus areira L.: Anti-inflammatory or pro-inflammatory effect - Davicino, Roberto Carlos (2010)
The anti-inflammatory drugs possess many serious side effects at doses commonly prescribed. It is really important to discover novel regulators of inflammation from natural sources with minimal adverse effects. Schinus areira L. is a plant native from South America and is used in folk medicine as an anti-inflammatory herb. For this study, the activity of aqueous extracts on inflammation and the effect on superoxide anion production in mice macrophages were assayed. Aqueous extracts were prepared by soaking herbs in cold water (cold extract), boiling water (infusion), and simmering water (decoction). Cold extract possess an anti-inflammatory activity. Decoction and infusion showed pro-inflammatory activity. Cold extract increased the production of superoxide anion. It has been proposed to use diverse methods to obtain extracts of S. areira L. with different effects. Cold extract, decoction, and infusion could be utilized as extracts or as pharmacological preparations for topical application.